PENGARUH LEVERAGE, UKURAN KAP DAN UMUR PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN YANG TERDAFTAR DI LQ-45 PERIODE 2017-2019 - Pedi Riswandi; Varrel Rachmad Gifari; Iwin Arnova (Jurnal Cakrawala Ilmiah, 2022)
This study aims to determine the effect of Leverage, KAP Size, and Company Age on audit delay in companies listed in LQ-45 for the 2017-2019 period. The sample taken using purposive sampling is 28 companies from LQ-45 companies in 2017-2019. so that the research data tested amounted to 84. The data analysis techniques used were descriptive statistics, classical assumption test, multiple linear regression analysis. Based on the results of the study, it shows that leverage has a significant effect on audit delay, while KAP size and company age have no significant effect on audit delay. Simultaneously, leverage, KAP size and company age have a significant effect on audit delay in companies listed on LQ-45 for the 2017-2019 period.